Faktor-Faktor Penyebab Kejadian Stunting pada Balita Usia 12-24 Bulan di Desa Karya Mulya, Provinsi Riau - Ayuni, Sri Susi; Rizqi, Eka Roshifita; Isnaeni, Lira Mufti Azzahri (Jurnal Ilmu Gizi dan Dietetik, 2024)
The factors that cause stunting in toddlers include incomplete immunization of toddlers, failure to provide exclusive breastfeeding or early weaning, and inappropriate provision of Complementary feeding (MP-ASI). The research aims to analyze the factors causing the incidence of stunting in toddlers aged 12–24 months in Karya Mulya Village in 2023. The type of research is quantitative with a cross-sectional design. The research was conducted in April 2023 with a sample size of 52 mothers of toddlers aged 12–24 months using a total sampling technique. Data were collected using questionnaires, Maternal Child Health books, and body length measurements. The data analysis used was univariate and bivariate analysis with the Fisher Exact Test. The results of the univariate analysis showed that 9 toddlers (17.3%) experienced stunting, 21 toddlers (40.4%) did not give exclusive breast milk at the age of 0–6 months, 27 toddlers (51.9%) gave complementary feeding incorrectly. The Fisher Exact Test results found that there was no relationship between complete immunization and the incidence of stunting (p-value=1.000), there was a relationship between exclusive breastfeeding and the incidence of stunting (p-value=0.002), there was a relationship between giving complementary feeding and the incidence of stunting (p-value=0.025). The conclusion is that there is no significant relationship between the completeness of immunization in toddlers, but there is a significant relationship between exclusive breastfeeding and Complementary feeding and the incidence of stunting in toddlers aged 12–24 months in Karya Mulya Village in 2023. It is hoped that mothers of toddlers will continue to monitor the growth of toddlers every month, providing routine immunizations, exclusive breastfeeding, and MP-ASI by guidelines to prevent stunting.